2, 4-D deposition is reduced and more variable immediately adjacent to cereal rye cover crop rows. (23rd August 2019) - Haramoto, Erin R.; Sherman, Austin D.; Green, Jonathan D.
Abstract: Horseweed, also known as marestail, is a problematic weed for no-till soybean producers that can emerge from late summer through the following spring. Overwintering cover crops can reduce both the density and size of fall-emerged weeds such as horseweed and reduce further spring emergence, although typically cover crops do not provide complete control. Cover crops may be integrated with additional spring herbicide applications to control emerged horseweed, and selective herbicides such as 2, 4-D may be used to target horseweed while maintaining small grain cover crop growth. However, cover crops may affect herbicide deposition, which could reduce their efficacy to control weeds. The objective of this study was to determine how the amount and variability of 2, 4-D ester spray solution deposition, measured with water-sensitive paper, was affected by a cereal rye cover crop and fall-applied saflufenacil. We also examined deposition at the soil surface relative to the cereal rye row position. In a year with greater cereal rye biomass accumulation, there was 44% less coverage and average deposit size was 45% smaller immediately adjacent to cereal rye rows compared with between rows and areas without cereal rye. Greater variability in these measurements was also noted in this position. Percent spray solution coverage was also 22% greater in plots that received saflufenacil in the fall, and deposits were 28% larger. In a year with less cover crop and winter weed biomass, no differences in spray deposition were observed. This suggests that small horseweed plants and other weeds immediately adjacent to cereal rye cover crop rows may be more likely to survive early spring herbicide applications, though the suppressive effects of cover crops may mitigate this concern.